Sunbelt/frostbelt : public policies and market forces in metropolitan development - Pack, Janet Rothenberg (James A. Johnson metro series., 2005)
"The product of a multiyear project looking at how government policies shape growth patterns in five metropolitan areas--Los Angeles, Phoenix, Pittsburgh, Chicago, and Philadelphia--this book examines how these sunbelt and frostbelt metro areas have tried to use policy reform to address their individual development challenges"--Provided by publisher